THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN RELIGIOUS STUDIES EXPERTISE: A LITERATURE REVIEW - Sarsebayeva R.A.; Meirbayev B.B. (Research Retrieval and Academic Letters, 2025)
This article presents a comprehensive literature review on the application of artificial intelligence in religious studies expertise, a field increasingly shaped by digital technologies and epistemic pluralism. Drawing on peer-reviewed sources indexed in Scopus and Web of Science the study identifies and analyzes five thematic clusters: (1) machine learning and digital governance, (2) robotics and Christian epistemology, (3) transhumanist imaginaries, (4) theological-ethical frameworks, and (5) digital religious authority. The findings reveal that AI systems are not merely analytical tools but active agents in reshaping how religious legitimacy, moral reasoning, and symbolic interpretation are constructed and contested. By synthesizing contributions across theological, legal, technological, and philosophical domains, the review argues for a broadened understanding of religious expertise one that is both critically adaptive to emerging algorithmic infrastructures and ethically responsive to cultural and confessional specificity. The article concludes with a call for interdisciplinary and context-sensitive approaches to ensure that AI integration in religious contexts promotes epistemic justice, theological coherence, and human dignity.